اور مطالعہ سیرت(karen Armstrong) کیرن آرم سٹرانگ - سمیہ اطہر (FIKR-O NAZAR فکر ونظر, 2012)
In the modern age, advanced means of communication have made the fundamental and authentic sources of knowledge accessable. Consequently, the orientalists and scholars studying these treasures of Islamic religious knowledge shelved in the libraries across the globe have been able to present positive and authentic view of Islam and its messenger. A number orientalists and non-Muslim scholars have consulted the basic sources and produce positive and unbiased biographies to the Prophet. As a part of this tradition of intellectual honesty, Karen Armstrong, a religious scholar of present day, has written two books on the Sirah of the Holy Prophet Muhammad (ﷺ). During the past two decades (especially post 9/11), a wide, deep gulf has emerged between West and the Muslim world. In this perspective, Karen Armstrong, having great knowledge of history, comparative religions and current international relations, has painted a very positive picture of Islam and the Prophet of Islam (ﷺ). She believes that the Prophet of Islam and his teachings can guide the world even today. The political and social problems, Western and Islamic world are facing, can be solved by following the path of the Prophet. This paper focuses particularly on this aspect of Karen's Sirah writing.